Actions and Conceptions: Exploring Initial Literacy Teaching Practice for Adults. Issue 5 (3rd September 2018) - Colliander, Helena; Ahn, Song Ee; Andersson, Per
ABSTRACT: Given that it is a delicate task to meet the educational needs of adult emergent readers in a second language setting, this study serves to explore the teaching practice of teachers working with learners of initial literacy and second language. Based on a situated learning perspective, data from 16 lesson observations of nine teachers is analysed. The findings show that teachers initiate and negotiate learning activities, strive to get the students to understand words and other symbols, facilitate participation within and outside the classroom and negotiate the acceptable student behaviour. These findings suggest that Literacy Education and Second Language Learning for Adults (LESLLA) teaching and learning is a particular practice, where the teachers' actions are intertwined with those of the learners and with the teachers' conceptions of the learners. In that way, the teachers' actions do not only speak of the learners, but also of their own professional identity.